Teacher skills – emotional intelligence skills profile - Correia, Ana Almeida (2012)
The current situation of education has changed: the social, economic and personal circumstances of the population require a more complex and demanding teacher than a few years ago (Hernández, 2007). Objective: To know the variables assigned to the competent teacher – through the perception of a sample of teachers - in order to create a profile in terms of effective teaching practice, for the present day. Method: A transversal, descriptive and qualitative study, using "grounded theory" methodology, with semi-structured interviews conducted to a purposive sample of 60 subjects: 7 preschool teachers and 53 primary and lower secondary school teachers aged 22 to 59, within 4 to 30 years of working experience. The discursive contents obtained were subjected to a content analysis, from which a "categorical tree" emerged defining the profile of the ideal teacher. Conclusions: The skills profile obtained shows three main categories: "Emotional Competence", "Personality Traits" and "Scientific and Teaching Competence". - The first, "Emotional Competence" with 226 discursive references (knowing how to read nonverbal language; paying attention, managing emotions/relationships; learning how to put oneself in the shoes of the student, being assertive; respectful, being positive; being creative…); - The second main category, "Personality Traits" with 115 discursive references (duteous; rigorous…); - The third main category refers to "Scientific and Teaching Skills" with 45 discursive references (updated scientific knowledge, appropriateness of strategies…).